Perancangan dan Implementasi Komunikasi RS-485 Menggunakan Protokol Modbus RTU dan Modbus TCP Pada Sistem Pick-By-Light - Tosin Tosin (Computer Engineering Departement, Universitas Komputer Indonesia, 2021)
The industrial process requires high productivity in every activity. An example is a process of taking items in the storage area. The current system is that the operator takes the items by manually searching in the storage. It will cause problems, namely, the process of taking items takes a long time or occurred a mistake in taking items. The purpose of this research is to design a pick-by-light system with RS-485 serial communication and TCP/IP using the Modbus protocol to support efficient production activities. Pick-by-light is a system consisting of a lightweight device as a sign that an item must be taken, a button to confirm that an item has been taken, and a processing device to process data. The result of this research shows that the pick-by-light system can work properly by implementing RS-485 serial communication with the Modbus Protocol and TCP/IP communication with the Modbus TCP protocol. These results are obtained from tests that have been carried out with different communications using RS-485 serial communication and TCP/IP. It can be applied to manufacturing and warehousing industries to increasing the productivity of items taking.